Investigation and Characterization of Residual Stress on Prestressed Steel I-Beams Manufactured by Welding - Özer, A.; Özçatalbaş, Yu. (Металлофизика и новейшие технологии, 2015)
The purpose of this study is to determine type and magnitude of residual stresses occurring on steel I-beams, which are manufactured by using prestressing with welding method. In order to achieve this purpose, 50, 100, 150, 200 and 272 MPa prestressed steel I-beams (PSIB) are manufactured. Residual stresses on these beams are determined with the hole-drilling method. As determined, the longitudinal residual tensile stress increases with increasing prestressing stress up to 200 MPa. As also detected, the residual tensile stress up to 92 MPa on crosscut in surface centre of lower flange occurs, and it converts to residual compressive stress through edges of lower flange. Moreover, residual compressive stress is determined at web of beam. This stress converts to tensile stress on lower flange, and this variability on stress type creates shearing stress on welding seam.